Kajian Rantai Nilai dan Analisis Nilai Tambah Jagung (Studi Kasus di Kabupaten Konawe, Provinsi Sulawesi Tenggara) - Julian Witjaksono (Jurnal Ilmu Pertanian Indonesia, 2017)
Maize is the essential crop in Southeast Sulawesi and also as the primary income resource for the smallholder farmers. This research was conducted in Amesiu Village, Pondidaha Sub District, of Konawe District. This study has employed descriptive method for supply chain, Hayami method for value added analysis and SWOT analysis. Study results show that maize boiled business is the highest value added and the lowest value added is the maize farmer (IDR303.900,00/kg and IDR9.900/kg respectively). Meanwhile, the middle men have value added about IDR235.960,00/kg. Margin analysis shows that the business men of boiled maize have the highest margin (IDR323.898,00/kg), the lowest margin is the maize farmer (IDR36.200,00/kg), meanwhile the middle men has margin value about IDR240.960/kg). SWOT analysis shows the strategy that should be implemented by the business men of boiled maize is to support aggressively growth policy (growth oriented strategy). This strategy is more focusing to SO strategy (Strength-Opportunity) by using power to implement the opportunity.